Trends in incidence and mortality of nasopharyngeal cancer in China (2004–2018): an age-period-cohort analysis - Chen, Xu; Xia, Wei; Xu, Zhi-Hui; Suo, Ya-Xi; Xie, Long (Frontiers in Oncology, 2025)
ObjectiveTo analyze the trends in incidence and mortality of nasopharyngeal cancer (NPC) in China and its age-period-cohort effect, providing evidence for developing prevention and control strategies for NPC.MethodsNPC data were obtained from the Chinese Cancer Registry Annual Reports covering the period from 2004 to 2018. Joinpoint Regression Software (version 4.9.0.0) was used to calculate the Average Annual Percent Change (AAPC) and their corresponding 95% confidence intervals (CI) to assess the trends in incidence and mortality rates. We analyzed the age-period-cohort model of NPC in the Chinese population and estimated the effect of age, period, and cohort on NPC incidence and mortality.ResultsThe incidence and mortality rates of NPC show a steady declining trend. The age-specific incidence curves for NPC in Chinese males and females both peaked in the 50–54 age group, while the age-specific mortality curves peaked in the 70–74 and 75–79 age groups for males and females, respectively. Using the 2009–2013 period as a reference, the period effect rate ratios (RR) for NPC incidence and mortality in males during 2004–2008 were both greater than 1 and higher than those in females. Additionally, the cohort effect RR values for overall NPC incidence and mortality in China showed downward trend.ConclusionOur study confirmed the effectiveness of NPC prevention and control strategies in China from 2004 to 2018. However, it underscores the need for targeted interventions among high-risk populations to further reduce the incidence and mortality rates of NPC.